(untitled) (Mustansiria Dental Journal, 2024)
Cervical enamel projections and enamel pearls in relation to molar furcations may act as predisposing factors in periodontal attachment loss. The objectives of this study were to investigate the prevalence of cervical enamel projections and enamel pearls on furcation areas of molar teeth of Iraqi population. The material consisted of (465)extracted upper and lower molars. They were (200) upper molars and (200) ) lower molars extracted because of` caries and pulp lesions(groupl), while the other molars extracted because they were periodontally diseased(group2). The cervical )64( enamel projections were classified into three grades(described according to peter et al 2000) For group l the results showed that (5l%) of upper molars and (66%) of lower molars had cervical enamel projections. Enamel pearls were identified on (1.5%) of upper molars and (2.5%) of lower molars. Maxillary molars had (59.8%) grade I cervicaljnamel pro`ections and 28.4%) grade ll and (ll.7%) rade III. While mandibular molars showed (66.6%) teeth with grade I, (24.2%) teeth with grade II and (9%) teeth with grade III .For grou 2 cervical enamel rojcctions were identified on (70.7%) ofthe collected molars The results of the present study give an indication that cervical enamel projections are frequent enough to be of clinical importance